Scattering and absorption of light by periodic and nearly periodic metallodielectric structures - V. Yannopapas; A. Modinos; N. Stefanou (Optical and Quantum Electronics, 2002)
We consider the effect of different approximations to the dielectric function of a silver sphere on the absorption of light by two-dimensional and three-dimensional periodic and non-periodic arrays of non-overlapping silver spheres in a host dielectric medium. We also present some results on the band structure and the absorption coefficient of light by photonic crystals consisting of non-overlapping silver-coated spheres in a dielectric medium.